The Strategic Value of Corporate Social Responsibility (CSR): Leveraging WSP Group’s CSR Strategy to Implement Its Sustainability Policy - Iskender, Khatira (2010)
Through its impact on the built environment, construction plays a central role in the UK government’s drive to promote sustainable growth and development. Therefore, Corporate Social Responsibility (CSR) has become a growing area of interest for engineering and design consulting firms, such as WSP, within the construction industry as their stakeholder bases expand and expectations regarding the firm’s conduct also rise. This paper investigates WSP’s approach to CSR by addressing the following three questions:  What constitutes a CSR in the engineering design consulting industry?  Can CSR be an educational mechanism for sustainability?  What factors influence the emergence of strategic CSR activities in implementing sustainability policy These questions explore how the WSP’s CSR strategy assists the company in thinking ‘outside-in’ about how it creates and sustains competitive advantage. Outside-in thinking, which sees the world from the perspective of stakeholders, is a powerful new lens through which the company’s leadership can discover new business opportunities and risks. I argue that the company can better anticipate changes in the business environment if it proactively addresses stakeholder issues by integrating its market issues with non-market issues which ultimately can lead the company to discover new sources of value through innovation and to achieve its sustainability goals. The paper finds that Michael Porter’s work of the 1980’s, ‘Competitive Strategies’, is a method that has been utilized by WSP to enhance CSR practices for the organization, through strategic CSR development.